Analysis of Unlawful Acts in Repeated Land Sales: Collaboration of Hamlet Head and Notary Negligence - Mahardika Dirgantara; Tjempaka Tjempaka (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2026)
Ideally, the transfer of land rights must be conducted before a Notary based on accurate data, with the Village Head providing factual information on land status. Their collaboration should ideally strengthen legal certainty. However, in reality, the practice of double sale of land (dubbel verkoop) remains prevalent due to collaboration between Village Heads who provide false statements and Notaries who neglect their verification duties. This study aims to analyze the construction of tort liability under Article 1365 of the Indonesian Civil Code. The research employs a normative legal method with a case study approach. The findings reveal that the collaboration between Village Heads and Notaries fulfills all elements of unlawful acts. Victims are entitled to legal certainty through the annulment of defective deeds as well as compensation for material and immaterial losses. Village Heads may be subject to Article 263 of the Criminal Code and Notaries to Article 264 of the Criminal Code.